Makna Ungkapan Yang Sulung Dalam Kolose 1:15 Sebagai Tanggapan Terhadap Pemahaman Kristologi Saksi Yehuwa - Jacob Timisela (Manna Rafflesia, 2021)
From the mid-19th century until now Christians are confused and troubled by the movements and teachings of the Witnesses who have undermined the Superiority of Christ. In particular when they interpret the word prototokos in Colossians 1:15 which is very different, even contrary to Christian understanding and beliefs in general. The results of this study found that there are differences in the basic and background interpretations used by Jehovah's Witnesses with the basis and background for the interpretation of Christians in general of the word prōtotokos in Colossians 1:15. Jehovah's Witnesses use the word qanah (קנח) from Proverbs 8: 22,25 as the basis and background for the interpretation of the word prōtotokos in Colossians 1:15.